2003
DOI: 10.1111/1475-3588.00051
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Training with Children and Young People: Theory, Evidence and Practice

Abstract: Deficits in social skills and social competence play a significant role in the development and maintenance of many emotional and behavioural disorders of childhood and adolescence. Social skills training (SST) aims to increase the ability to perform key social behaviours that are important in achieving success in social situations. Behavioural SST methods include instructions, modelling, behaviour rehearsal, feedback and reinforcement, frequently used in association with interpersonal problem solving and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
257
0
69

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(330 citation statements)
references
References 81 publications
4
257
0
69
Order By: Relevance
“…However, until now, no study has examined the association between QoL and these factors in children with psychiatric problems. Further, this study examined whether other child factors -intelligence, and poor social skills -were correlated with QoL, because previous studies found an association between these factors and level of psychopathology [9,10]. It is likely that these factors also affect QoL, although this has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, no study has examined the association between QoL and these factors in children with psychiatric problems. Further, this study examined whether other child factors -intelligence, and poor social skills -were correlated with QoL, because previous studies found an association between these factors and level of psychopathology [9,10]. It is likely that these factors also affect QoL, although this has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…This makes them feel important, and facilitates the reflection on feelings and the increase of self-esteem (Castanyer, 2004). All these studies show the importance of the assertive (Evans, Langberg & Williams, 2003;Spence, 2003). The major challenge of this type of interventions is the opportunity to change social behaviors, in such a way that they can extend from the setting into the daily social interactions (Barrett, Lock & Farrel, 2005;Coplan et al, 2010;Evans et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…One of the main components of SIT is self-instructional training (Meichenbaum, 1975), which guides peoples' behavior through self-talk, which gradually becomes self-generated and habitual. Self-instructional training has shown to be effective in the control of impulsive behavior (Durlak, Fuhrman, & Lampman, 1991) related to attention deficit (Spence, 2003). Asnaani, Vonk, Sawyer, & Fang, 2012).…”
Section: Social Running Head: a Pilot Stress-management Program To mentioning
confidence: 99%